The Predictors of Awareness of Sexual Abuse and Sexual Violence in the Media and the Influence on Actions of the Individuals - Frentzen, Engie; Reisacher, Doris; Brähler, Elmar; Rassenhofer, Miriam; Fegert, Jörg M.; Witt, Andreas (Frontiers in Psychiatry, 2022)
Introduction The number of reportings on sexual abuse (SA), sexual violence (SV) cases covered in the media has risen a significant amount with most cases involving women and children. The aim of the study is to explore the questions: Are people aware of sexual abuse and sexual violence in the media? What are the predictors of awareness of sexual abuse and sexual violence? Does the awareness of sexual abuse and sexual violence in the media affect the actions of the individuals? Methods A representative survey of the German-speaking resident population (2020) on physical and mental well-being was used. The participants (N=2503: females =50.9%) were between the ages of 14 and 97 (M=49.81). The German version of the Adverse Childhood Experiences Questionnaire, The General Habitual Well-Being Questionnaire and questions about own experiences of sexual harassment on the internet, experiences of domestic sexual abuse and different socio-economic variables were used. The outcome variables regarding the awareness of SA and SV in the media, different types of scandals (church, pedophile, USA), #MeToo-debate and the change in actions were used. Frequency analyses and binary regressions were conducted. Results 1555 (62.6%) respondents answered yes to being aware of SA and SV in the media. The results show that females, aging, number of children in household, Protestant and Catholic religion, school graduation, own experience(s) of sexual harassment on the internet, own experience(s) of SA in childhood, and Adverse Childhood Experiences have a significant higher association to the awareness of SA and SV in the media. German nationality and Muslim religion have a significant lower association. The variables that most commonly affected the awareness of SA and SV, scandals, debate and the individual actions were age, own experiences of sexual harassment on the internet and the Protestant religion. Conclusion Advertising more support centers, hotlines and linking this information to sexual abuse cases covered in the media should be considered. Media bystander interventions could be helpful to train people to react appropriately. Further investigation that considers the different types of media and its influence on the awareness of SA and SV is needed.